THE INFLUENCE OF FORM AND MATERIALS ON THE PROPER ACOUSTIC FUNCTION OF THEATRICAL PERFORMANCES AND MUSIC CONCERTS AT GEDUNG KESENIAN IN JAKARTA - Mega, Susanti (Jurnal Riset Arsitektur, 2017)
Abstract- A given space requires a specific design for it to function in the best possible way. Many aspects need to be taken into consideration, and the same principle applies to an auditorium. Its space requires proper handling of the right acoustics to optimize the activities to be held there, among others space employed for the purpose of staging theatrical performances and concerts. Ideally speaking, these activities must prioritize the use of natural (purely acoustic) sound without resorting to an electric amplifier. Therefore, an appropriate acoustic design of the space to be used is of the utmost necessity. Each of these spaces has its own criteria to optimize the activities that are held there. To examine the acoustic quality of a given space, there are several prerequisites that must be fulfilled, starting from the form and materials used, the sound’s volume level, sound distribution, reverberation time, acoustic flaws or shortcomings and noise reduction or sound control. Using the explorative method and post-performance evaluation, this research study investigates the capability of the Arts Building called Gedung Kesenian in Jakarta to accommodate two different activities, both from the angle of the specific activity and the prerequisites for the space used. Gedung Kesenian Jakarta has attempted to surmount the problem of echo/reverb that is different for the theatrical and musical performances. However, the too widely diverging values have prompted the need for adding portable elements that are passive in nature in order to maximize the sound reflection, evenness of sound distribution, reverb time as well as dealing with the problem of the echoing sound area, referred to as “shadow sound”.Keywords: acoustic suitability, acoustics of theater space, acoustics of concert space, reverberation time